Management Accounting Practices by Some Selected Manufacturing Enterprises Enlisted in Chittagong Stock Exchange, Bangladesh: An Evaluation - Hossain, Md. Musharof; Ahmmed, Monir; Hossain, Mohammad Emdad; Azam, Md. Kazi Golam (Journal of Asian Business Strategy, 2020)
Management accounting (MA) helps to formulate strategies in manufacturing enterprises (ME). This paper is the outcome/product of a study on the Management Accounting Practices (MAP) of Nine (9) manufacturing enterprises from 4 sectors listed in the Chittagong Stock Exchange (CSE) on the year of 2019. The study aims to evaluate the present scenario of MA practices. The primary data were collected through a structured questionnaire from 139 respondents selected from nine enterprises and found that the highest mean score was 4.71, on Management accounting information is very essential for manager to take decision making and lowest mean score is 4.28, for the practice of management accounting to enhance profitability and the average mean score was 4.4871 in the scale of 5. The study also revealed that about 59% to 98% of enterprises have disclosed the management accounting information both in descriptive & monetary nature. New and innovative techniques of management accounting should be implemented to gain competitive advantages. The study has recommended improving the management accounting practices in this regard.